032 Rates of cognitive difficulties in children with medically unexplained symptoms attending specialist services. (December 2018) - Gosling, C; Taylor, C; Heyman, I; Stark, D
Abstract : Background: Medically Unexplained Symptoms (MUS) are physical symptoms with no identifiable medical cause. Whilst there are multiple pathways into MUS, current conceptualisations highlight the role of psychological factors in the aetiology and maintenance of symptoms (Wileman & Chew-Granham, 2002). Recent studies highlight the high-rates of neurodevelopmental and mental-health conditions amongst children with MUS; including intellectual disability (26%), ADHD (22%) and specific learning disorders (14%–38%). There are also high-rates of co-occurring mental health disorders (˜66%, Reilly, 2003; Yadav, 2015). Unidentified cognitive difficulties are thought to represent a significant contributory factor to the aetiology and maintenance of MUS, with psychological stress being a purported mechanism (Wileman & Chew-Granham, 2002). Objective: The aim of the current study was to Investigate the rates of cognitive difficulties amongst children with MUS attending a Tier 4 Specialist Service. Investigate levels of academic attainment Investigate levels of adaptive behaviour and executive function on parental–report measures. Method: All children with MUS visiting a Tier 4 Specialist Service for a cognitive assessment between May 2013 and December 2017 were included. Demographic and diagnostic information was extracted. Scores on cognitive assessments lower than one standard deviation (SD) from the normative mean were classified as clinically significant. Results: Over 63% of children had Full-Scale IQ scores more than one SD below the mean. A similar proportion generated low-scores on measures of attention, visuomotor integration and executive function. Over half (54%) of the sample had low-levels of adaptive behaviour. There were a high-rate of academic difficulties, particularly in mathematics proficiency (37%) and reading comprehension (52%). Conclusion: Compared to a normative population, children with MUS had high rates of intellectual, cognitive and academic difficulties, alongside Low levels of adaptive behaviour. It is possible that intervention and support for such difficulties may reduce the severity of MUS and resulting impairment.